Digital Transformations of Illicit Drug Markets Reconfiguration and Continuity (2023)
Digital Transformations of Illicit Drugs Markets: Reconfiguration and Continuity considers how the digital revolution has changed the selling and buying of illicit substances through increased convenience and anonymisation. Providing a uniquely interdisciplinary perspective, this book shows how the digital transformation of illicit drug markets combines a reconfiguration of how sellers and buyers interact in new markets alongside the continuity of embeddedness of market structures in cultural, economic, political and legal realms. Emphasising that illicit digital markets are embedded in societal structures and power relations in general, contributors also recognise the importance of critical perspectives on inequalities between the Global North and South as well as issues of gender.